Heat and microwave reflux extraction, optimization, and physicochemical characterization of oleoresins from Malaysian pepper (piper nigrum) - Olalere, Olusegun Abayomi (2018)
Emerging evidence has revealed the undeniable ability of functional plants for the treatment of many degenerative free radical-related diseases in ethnomedicine. Black and white peppers (Piper nigrum) are examples of such plants with both nutritional and medicinal properties. The free radical scavenging properties of these important commodity crops is due to the presence of various mineral elements and phenolic compounds. A need then arises to find an efficient extraction technique that gives high quality phenolic extracts at optimum condition. In this study, heat reflux extraction (HRE) and microwave reflux extraction (MRE) techniques were compared for the extraction of oleoresins from black and white pepper. The effects of these extraction methods on the extraction yield, elemental composition, phenolic content, antioxidant activities, microstructure, and functional characteristics were succinctly investigated. The performance of the two extraction techniques were thereafter evaluated at different operating levels. This was achieved firstly by examining the effects of different parameters on both the extraction yield and absorbed energy, using a single factor experiment (SFE) and Taguchi orthogonal design of experiment (TODOE). The result obtained revealed that the MRE presented a better extracts than HRE in terms of fixed oil extracted, total phenolic content, antioxidant capacity, number of phenolic compounds and mineral elements. The estimated performance index adjudged MRE to be four times and six times better than HRE in black and white pepper refluxation, respectively. Moreover, white pepper offered a better and quality natural antioxidants in terms of the quantity of fixed oil, total phenolic content, antioxidant capacity, number of phenolic compounds and mineral elements. This research therefore provided an optimized, qualitative and quantitative insight into the effects of conventional and non-conventional extraction techniques on the yield, mineral composition, phenolic content, antioxidant activities, morphological and functional characteristics of black and white pepper extracts.